Dampak Perubahan Garis Pantai terhadap Status Titik Dasar dan Garis Pangkal Indonesia: Studi Kasus Nias Utara, Pulau Wunga, dan Bireun, Indonesia - Kadafi Anantri, Nofal Mahdi; Djunarsjah, Eka; Putra, Andika Permadi (Fakultas Seni Rupa dan Desain ITB, 2025)
Beach is a very dynamic environment because, in that environment, various processes occur, such as sedimentation, abrasion, and transportation. Likewise, the shoreline has a dynamic nature to change. Shoreline Changes can affect a country's maritime boundaries. This is because the changing shoreline can change the draw of the Baseline, which is the reference for measuring the maritime boundary. Therefore, it is necessary to monitor the shoreline where the Basepoint and Baseline are located. In this study, measurements of shoreline changes were made using SPOT 6 data which has a spatial resolution of 1.5 m. Shoreline changes were calculated using the DSAS. From the calculation results, the average rate of accretion in the Base Point 167 area is 5.63 m/year. Then in the area around Base Point 168 it has an average accretion rate of 2.27 m/year. In the area around Base Point 180, an average accretion rate of 15.11 m/year is obtained. The accretion process results in a change in the shoreline, resulting in a change in the configuration of the low water line which is the location where the base point is placed. Thus, changes in the shoreline can affect the withdrawal of Indonesia’s maritime boundaries.